Evaluation of wound healing potential of crude extracts of zyziphus oenolpia l. Mill (indian jujuba) in wistar rats - Pulak Majumder (International Journal of Phytomedicine, 2012)
Zyziphus oenoplia is a perennial shrub used in traditional medicine for treating hyper acidity, Ascaris infection, stomachalgia and healing of wounds. The objective of this study was to investigate the root extracts of this plant, to evaluate their wound healing potential in rats. Excision, Incision and Dead space wound modals were used to evaluate the wound healing activity of the extracts on wister rats. In each modal, animals were divided into six groups of six animals. Each model, group I & II served as control and reference standard. In wound models, group III, IV, V and VI animals were treated with plant root extracts (300 and 400mg/kg/day) for 18 days and 10days respectively. The vehicles effect on the rate of wound healing were assessed by the wound closure rate, epithelialisation period, tensile strength, granulation tissue weight, hydroxyproline content and histopathology of granulation tissue. The ethanol extract of plant root promoted wound healing activity significantly in all the wound modals. High rate wound contraction (P<0.001), decrease in the epithelialisation period (14.67±0.33), high skin breaking strength (501.53±2.18g), significant increase in granulation tissue weight (P<0.001) and hydroxyproline (P<0.001) content were observed in ethanol root extract. Histological studies of the granulation tissues of the ethanolic extract treated group showed the lesser number of inflammatory cells, and increase collagen formation than the control and also compared with other groups. Phytoconstituents like flavanoids, alkaloids, steroids, triterpenoids, saponins etc were also confirmed by phytochemical test. The data obtained in this investigation indicated that the ethanolic root extract possesses better wound healing activity and it can treat different types of wounds in human being too.